MAKNA LAFAZH QAUL DAN KALÂM DI DALAM AL-QUR’AN MENURUT PERSPEKTIF ILMU BALAGHAH - Murdiono, Murdiono; Hasaniyah, Nur; Taufiq, Hadi Nur (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
This study analyzes lafazh qaul and